Effect of SCADA Implementation to Productivity in Ammunition Industry: A Review - Sanjiwani, Yudistira; Risonata, Victor Yuardi; Afif, Ilham; Subarkah, Salim (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2020)
Within the last years, global industries are hyping over Industry Revolution 4.0. Utilizing the computer science combining with the mechatronics, each industry strives to increase productivity and efficiency. Of those industries is the ammunition industry. Regarded as one of the strategic industry of a nation, the ammunition industry needs to quickly adapt to the technological advance, the beginning of a new era. The old-schooled method in production control is outdated and needs to be replaced. Supervisory control and data acquisition (SCADA), one of the newest method for production control, has been developed for several years. The exact form of implementation is however yet fixed. It has to be specifically developed for each industry, i.e. the ammunition industry in this case. With the rapidly growing information technology and science, the ammunition industry is expected to be able to implement the best suited control system to increase and to optimize its production capacity.